Analisis Pelaksanaan Pembelajaran Pemrosesan Informasi Dalam Mata Pembelajaran Sejarah Di Kelas XI Madrasah Aliyah Al-Muttaqin Kabupaten Kapuas Hulu - Muhamad Sadikin; Tonny Iskandar Mondong; Mohamad Wantu (Universitas Negeri Gorontalo, 2021)
The purpose of this study was to determine the Implementation of Information Processing Learning in History Subjects in Class XI Madrasah Aliyah Al-Muttaqin, Kapuas Hulu Regency for the 2012/2013 academic year. based on a population of only 93 people, the entire population was taken as a sample so that this study was a population study. The data collection tools used were observation guides, questionnaires, interview guides, syllabus and lesson plans. Data processing and data analysis is known. Preparation of the implementation of information processing learning by history teachers is classified as very good with the results obtained by 85.7%. The implementation of information processing learning by history teachers is classified as very good with a result of 80.1%. Evaluation of the implementation of information processing learning by history teachers is classified as good with a result of 74.8. For this reason, information processing learning in history subjects needs to be continuously applied and developed in other materials so that the planned learning objectives can be achieved effectively.